Effects of football training on cognitive performance in children and adolescents: a meta-analytic review - Fan Mao; Fan Mao; An Yin; Shan Zhao; Qun Fang; Qun Fang (Frontiers in Psychology)
BackgroundThe cognitive development of children and adolescents is crucial for their academic success and overall well-being. Physical activity has been linked to improved cognitive performance, but the specific effects of football training on cognitive function in this population remain unclear. This meta-analytic review aimed to comprehensively evaluate the impact of football training on cognitive performance in children and adolescents.MethodsLiterature was searched through PubMed, PsycINFO, SPORTDiscus, Embase, and Web of Science. Eligible studies were randomized controlled trials (RCTs) or crossover designs assessing cognitive performance following football training interventions. Outcome measures included attention, inhibitory control, and working memory. Data synthesis and meta-analysis were performed to determine the overall effect sizes.ResultsTwelve studies were included in the meta-analysis, comprising 1,574 children and 94 adolescents. Football training demonstrated moderate, statistically significant effects on attention (Hedges’ g = −0.77, p = 0.01), inhibitory control (Hedges’ g = −0.67, p = 0.02), and working memory (Hedges’ g = −0.44, p = 0.03). The findings suggest that football training positively influences cognitive performance in children and adolescents.ConclusionFootball training holds promise for enhancing cognitive function in children and adolescents, particularly in attention, inhibitory control, and working memory. Theoretical frameworks emphasizing environmental enrichment, cardiovascular fitness, and cognitive component skills help elucidate the underlying mechanisms. Future research should explore how football training compares to other sports and assess whether integrative drills that combine cognitive elements with skill practice offer greater cognitive benefits than skill training alone. These insights support the inclusion of football in educational programs to foster cognitive development.